Psychosocial profile of candidates for bariatric surgery and its association with Binge-Eating Disorder - Coelho, Amanda Frazão (2021)
Objective: To describe the psychosocial profile of candidates for bariatric surgery, verify the prevalence of Binge-Eating Disorder (BED) and analyze the correlation between psychosocial variables in patients with or without BED. Methods: Cross-sectional study. Data collection was based on information from 125 patients, and the Periodic Binge-Eating Scale (BES) was applied by the Psychology section of a general hospital in southern Minas Gerais from July 2019 to March 2020. Candidates were separated into groups with and without BED, and psychosocial variables were correlated with groups. Results: The BED prevalence was 41.6% (52). Most patients were women (101; 80.8%), between 30 and 49 years (68; 54.4%), had a paid job (80; 64%), had completed or incomplete high school (51; 48.8%), reported memories of "remarkable facts" in the child's family environment (78; 62.4%). Anxiety disorders were reported in 37.6% (47) and depressive disorders in 17.6% (22) of the sample. As for weight-loss treatments, 62.4% (78) tried at least three types; 58.4% (73) reported the perception of weight gain in childhood or adolescence. A statistically significant association was observed between BED and a low education (p = 0.009). Conclusion: It was possible to characterize the studied population. It was observed that education can be considered a protective factor for the occurrence of BED.